Maintenance engineering and management : A guide for designers, maintainers, building owners and operators, and facilities managers /: A guide for designers, maintainers, building owners and operators, and facilities managers. ([2014]) - Harris, Jo, 1972-; Chartered Institution of Building Services Engineers,
No abstract available